Sosialisasi Tata Tertib Perpustakaan Sekolah di SDN 03 Ketindan Kab. Malang - Ubaidillah Ubaidillah; Yessi Ervina; Yuliana Yuliana; Styo M. W. Aji (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
A library in an elementary school (SD) is an educational facility that provides a variety of reading materials and learning resources that are appropriate to the age and level of development of students. Running a library requires human resources and adequate facilities and infrastructure. Rules and regulations in libraries are important for maintaining peace and order, protecting collections and facilities, and ensuring fair access for all users. results of observations in the library at SDN 03 Ketindan, Ke. Lawang, Kab, Malang which was carried out in June 2014. It was found that there were still many violations of rules and discipline committed by library visitors. These violations can be in the form of minor violations or major violations. The ultimate goal of this socialization is so that student visitors can access library facilities in an orderly manner so that reading and studying activities in the library run optimally. Activities were carried out with lectures and door to door outreach from class 1 to class 6. In general, the activities were carried out well by 85% with various supporting factors. Meanwhile, 15% of activities have not been implemented optimally due to various inhibiting factors such as technical material, readiness of presenters, and also heterogeneity of students targeted for service activities.